Improved STR analysis of degraded DNA from human skeletal remains through in‐house MPS‐STR panel. Issue 18 (16th August 2020) - Cho, Sohee; Shin, Kyoung‐Jin; Bae, Su‐Jin; Kwon, Ye‐Lim; Lee, Soong Deok
Abstract: DNA analysis of degraded samples and low‐copy number DNA derived from skeletal remains, one of the most challenging forensic tasks, is common in disaster victim identification and genetic analysis of historical materials. Massively parallel sequencing (MPS) is a useful technique for STR analysis that enables the sequencing of smaller amplicons compared with conventional capillary electrophoresis (CE), which is valuable for the analysis of degraded DNA. In this study, 92 samples of human skeletal remains (70+ years postmortem) were tested using an in‐house MPS‐STR system designed for the analysis of degraded DNA. Multiple intrinsic factors of DNA from skeletal remains that affect STR typing were assessed. The recovery of STR alleles was influenced more by DNA input amount for amplification rather than DNA degradation, which may be attributed from the high quantity and quality of libraries prepared for MPS run. In addition, the higher success rate of STR typing was achieved using the MPS‐STR system compared with a commercial CE‐STR system by providing smaller sized fragments for amplification. The results can provide constructive information for the analysis of degraded sample, and this MPS‐STR system will contribute in forensic application with regard to skeletal remain sample investigation.